DNA replication licensing in somatic and germ cells. - Eward, K; Obermann, E; Shreeram, S; Loddo, M; Fanshawe, T; Williams, C; Jung, H; Prevost, A; Blow, J; Stoeber, K; Williams, G (2004)
The DNA replication (or origin) licensing system ensures precise duplication of the genome in each cell cycle and is a powerful regulator of cell proliferation in metazoa. Studies in yeast, Drosophila melanogaster and Xenopus laevis have characterised the molecular machinery that constitutes the licensing system, but it remains to be determined how this important evolutionary conserved pathway is regulated in Homo sapiens. We have investigated regulation of the origin licensing factors Cdc6, Cdt1, Mcm2 and Geminin in human somatic and germ cells. Cdc6 and Cdt1 play an essential role in DNA replication initiation by loading the Mcm2-7 complex, which is required for unwinding the DNA helix, onto chromosomal origins. Geminin is a repressor of origin licensing that blocks Mcm2-7 loading onto origins. Our studies demonstrate that Cdc6, Cdt1 and Mcm2 play a central role in coordinating growth during the proliferation-differentiation switch in somatic self-renewing systems and that Cdc6 expression is rate-limiting for acquisition of replication competence in primary oocytes. In striking contrast, we show that proliferation control during male gametogenesis is not linked to Cdc6 or Mcm2, but appears to be coordinated by the negative regulator Geminin with Cdt1 becoming rate-limiting in late prophase. Our data demonstrate a striking sexual dimorphism in the mechanisms repressing origin licensing and preventing untimely DNA synthesis during meiosis I, implicating a pivotal role for Geminin in maintaining integrity of the male germline genome.